1973
DOI: 10.1210/endo-92-1-265
|View full text |Cite
|
Sign up to set email alerts
|

Progestin Production during Superfusion of Ovaries from Cycling Rats

Abstract: Superfusion of partially sliced ovarian tissue from cycling rats using a continuous flow of buffered saline was found to be a useful method for in vitro experimentation. The major metabolite of 3 H-progesterone (P) formed by superfused tissue was 20a-dihydroprogesterone (20aOH-P). Tissue from rats at all stages of the estrous cycle released detectable amounts of both P and 20aOH-P, with the latter steroid predominating. The 20aOH-P/P ratio was highest with proestrus and estrus tissue. The progestins were produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1974
1974
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In consequence, progesterone secretion could not be associated with luteinization and must be considered as a normal attribute of mouse follicles. This suggestion is sup¬ ported by a report that in vitro superfused slices of rat ovarian tissue released detectable amounts of progestins at all stages of the oestrous cycle (Anderson et al, 1973). However, the reported increase in progestin secretion and associated decrease in oestrogen release by clumps of follicles towards the end of a much longer culture period of mouse ovarian follicles (Qvist et al, 1990) is strongly suggestive of luteinization.…”
Section: Discussionmentioning
confidence: 94%
“…In consequence, progesterone secretion could not be associated with luteinization and must be considered as a normal attribute of mouse follicles. This suggestion is sup¬ ported by a report that in vitro superfused slices of rat ovarian tissue released detectable amounts of progestins at all stages of the oestrous cycle (Anderson et al, 1973). However, the reported increase in progestin secretion and associated decrease in oestrogen release by clumps of follicles towards the end of a much longer culture period of mouse ovarian follicles (Qvist et al, 1990) is strongly suggestive of luteinization.…”
Section: Discussionmentioning
confidence: 94%
“…The considerable variation in response to gonadotrophin between experiments gave some cause for concern, and was also noted by Anderson et al (1973) in their studies with superfused rat ovaries. A possible explanation for this variation in the present system has been obtained in recent experiments in which the binding of 125I-labelled-LH to porcine luteal tissue was studied under identical superfusion conditions (Leask, Watson & Anderson, 1974).…”
Section: Discussionmentioning
confidence: 96%
“…Preliminary results of these studies have already been reported Watson, Leask, Alam & Adams, 1973), and during the course of this work the technique has also been applied to the study of ovarian steroidogenesis in cyclic rats (Anderson, Turnipseed & Ungar, 1973).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation